1984
DOI: 10.1111/j.1751-908x.1984.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Precious Metals in some Geological Standards by Flameless A.A. Spectroscopy

Abstract: Precious metals (Ag, Au, Pt, Pd, Rh) were determined by flameless absorption atomic spectrornetry. Aqua regia sample decomposition followed by Te coprecipitation was employed to preconcentrate the precious metals in geological materials. With 5 g sample take‐up, the limits of determination were 1‐2 ppb for Au, Pd and Rh, 5 ppb for Ag and 10‐20 ppb for Pt. These elements were determined in some geochemical standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This work confirms also the conclusion presented by Signiholfi et al (9) that a partial attack with aqua regia usually ensures almost the total solubilization of precious metals (at least for gold and palladium) from geological materials.…”
Section: Resultssupporting
confidence: 91%
“…This work confirms also the conclusion presented by Signiholfi et al (9) that a partial attack with aqua regia usually ensures almost the total solubilization of precious metals (at least for gold and palladium) from geological materials.…”
Section: Resultssupporting
confidence: 91%
“…The method of co-precipitation with Te (Fryer and Kerrieh 1978;McHugh 1983;Sighinolfi et al 1984) was found to be effective and satisfactory to pre-concentrate Pt, Pd and Au, and to isolate them from the sample matrices. Hydrogen sulfide was instantly converted into NariS by reaction with NaOH.…”
Section: Analytical Methodologymentioning
confidence: 99%
“…After the gold is solubilized its separation from matrix elements is achieved by solvent extraction into methyl isobutyl ketone (MIBK), 36,37 co-precipitation on tellurium 38 or mer- cury 39 to avoid interferences at the measurement stage and to effect preconcentration. Using a 2 g sample Balaram et al 30 reported a rapid multi-acid digestion procedure utilizing mixtures of AR, Br 2 , HF, HClO 4 and H 2 O 2 which is amenable for batch analysis.…”
Section: Goldmentioning
confidence: 99%